Spatial Exploration of Age Distribution in Catalan Municipalities - Daniel Liviano; Josep-Maria Arauzo-Carod (European Regional Science Association (ERSA), 2012)
This paper takes the shelf and digs into the complex population's age structure of Catalan municipalities between 1999 and 2009. Catalonia is a very heterogeneous territory, and age pyramids vary considerably across different areas of the territory, existing geographical factors shaping municipalities' age distributions. By means of spatial statistics methodologies, this piece of research work tries to assess which spatial factors determine the location, scale and shape of local distributions. The results show that there exist different distributional patterns across the geography according to specific determinants.
Keywords: 330